Interpersonal and Affective Facets and Items of the Psychopathy Checklist-Revised (PCL-R) in Predicting Child Sex Offending*An earlier version of this study was presented at 2019 Annual Meeting of the American Society of Criminology. - Sohn, Ji Seun (Journal of interpersonal violence, 2022)
Psychopathy of child sex offenders in non-Western and Asian population is not frequently reported. The study examined psychopathic traits assessed by the Psychopathy Checklist-Revised (PCL-R) in three groups of male offenders, child sex offender, adult sex offender, and nonsex offender groups. Out of 451 offenders included in the sample, 445 recidivated after a follow up of 11 years: 27 child sex offenders, 174 adult sex offenders, and 244 nonsex offenders. Adult sex offenders scored higher in four facets and total scores compared with nonsex offenders. Child sex offenders had more problems in interpersonal (facet 1) and affective (facet 2) traits than nonsex offenders. More specifically, child sex offenders scored higher in failure to accept responsibility (item 16, Cohen?s d = 0.80) and callous/lack of empathy (item 8, Cohen?s d = 0.59) of facet 2 and pathological lying (item 4, Cohen?s d = 0.58) and glibness/superficial charm (item 1, Cohen?s d = 0.48) of facet 1 than nonsex offenders. Both child sex offenders and adults sex offenders were found to be more psychopathic than nonsex offenders. While facets 1, 2, and 3 did not separate child and adult sex offending, child sex offenders scored significantly lower in antisocial problems (facet 4) than adult sex offenders. Despite the limitation of using a sample of mostly high-risk offenders, our findings indicate that higher PCL-R scores in specific facets (1 and 2) and items (1, 4, 8, and 16) are more predictive of child sex offending and suggest insight for treatment strategies of child sex offenders.